1987
DOI: 10.1128/iai.55.12.3225-3227.1987
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the structural gene encoding the SH-activated hemolysin of Listeria monocytogenes: listeriolysin O is homologous to streptolysin O and pneumolysin

Abstract: By immunoblotting with an antiserum raised against purified listeriolysin O, we have detected the presence of a truncated protein of 52 kilodaltons in culture supernatants of a Tn1545-induced nonhemolytic mutant of Listeria monocytogenes (J.L. Gaillard, P. Berche, and P. Sansonetti, Infect. Immun. 52:50-55, 1986). The region of insertion of the transposon has been cloned and sequenced. The transposon had inserted in an open reading frame the listeriolysin O gene. The deduced amino acid sequence of this open re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(53 citation statements)
references
References 13 publications
1
52
0
Order By: Relevance
“…Bacteria tested included Streptococcus pyrogenes and Strep. pneumoniae, both of which produce haemolysins antigenically related to listeriolysin 0 (Mengaud et al 1987). No amplification product, as determined by gel electrophoresis, was detected for strains other than those of L. monocytogenes when stringent annealing conditions were employed during DNA amplification.…”
Section: Resultsmentioning
confidence: 98%
“…Bacteria tested included Streptococcus pyrogenes and Strep. pneumoniae, both of which produce haemolysins antigenically related to listeriolysin 0 (Mengaud et al 1987). No amplification product, as determined by gel electrophoresis, was detected for strains other than those of L. monocytogenes when stringent annealing conditions were employed during DNA amplification.…”
Section: Resultsmentioning
confidence: 98%
“…L. monocytogenes invades host cells either passively via phagocytosis or actively by expressing surface proteins that induce bacterial internalization (Cossart, 2011). Once inside the cell, L. monocytogenes is initially contained in a vacuole from which it rapidly escapes by expressing the pore-forming cytolysin listeriolysin O (LLO), two additional phospholipases, PlcA and PlcB, and components of the Com system (Mengaud et al, 1987;Goebel et al, 1988;Portnoy et al, 1988;Geoffroy et al, 1991;Leimeister-Wachter et al, 1991;Rabinovich et al, 2012). In the host cell cytosol, L. monocytogenes replicates and gains mobility via polymerization of host actin filaments, enabling the bacteria to spread from cell to cell without being exposed to the extracellular environment (Tilney and Portnoy, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…The difference of specificity between lmo0460 sequence and hlyA maybe originated from different mining strategies. The hlyA encoding hemolysin has been used to be a molecular marker for detection of L. monocytogenes for many years; this is because the transposon mutagenesis studies had indicated that the sulfhydryl-activated hemolysin is an important virulence factor for L. monocytogenes in 1986 (Gaillard et al 1986;Mengaud et al 1987), and hlyA encoding hemolysin had been identified and sequenced from a serotype 1/2a L. monocytogenes strain by Mengaud andcolleagues in 1987 (Mengaud et al 1987). Obviously, based on only transposon mutagenesis analysis, hlyA had been a molecular marker for detection of L. monocytogenes without bioinformatics analysis in the 1980s because the first microbial genome was sequenced in the 1990s (Fleischmann et al 1995); therefore, specificity of hlyA for L. monocytogenes could not have been evaluated in genomic level.…”
Section: Discussionmentioning
confidence: 99%